2016
DOI: 10.1177/1527002514551801
|View full text |Cite
|
Sign up to set email alerts
|

You Lose, I Feel Better

Abstract: This study considers the game-related performance of two listed soccer clubs in Italy which share the same stadium: Roma and Lazio. We introduce the performance of the archrival in the analysis. The high level of rivalry in sports should lead to a feeling of pleasure at the suffering of another group (known in German as Schadenfreude) and we assume to see the satisfaction of investor fans with the defeat of the archrival. Likewise, the win of the archrival can have a negative impact on the mood of investors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This fact by itself implies a behavioral bias since a positive news should normally be a negative news for the other competing clubs. For example, Demir and Rigoni (2017) show the effects of rival team's performance on the fan investors of a team.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact by itself implies a behavioral bias since a positive news should normally be a negative news for the other competing clubs. For example, Demir and Rigoni (2017) show the effects of rival team's performance on the fan investors of a team.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…It is concluded that proportion of variation in stock prices explained by match results is very small for 19 English clubs. Demir and Rigoni (2017) are the first introducing the performance of the archrival on stock market reaction to soccer performance analysis for Italy. They find that when club supporters experience the negative performance of their team, the results of their archrival affect their investment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Demir and Danis (2011) analyze this issue before but with different results. In particular, Demir and Rigoni (2017) find that stock markets react more reliably to the effects of European competitions than to that of the domestic ones. However, Demir and Danis (2011) find that stock markets do not react differently to the results of the European and local (Turkey) leagues.…”
Section: Introductionmentioning
confidence: 90%
“…Clubs receive their revenues mainly from competitions in which they participate. However, they also receive a substantial amount of revenues from merchandising, sponsors, and media contracts (Demir & Rigoni, 2017). More intense domestic and international competitions motivate clubs to generate more revenues (Demir & Danis, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation